Hybrid Bio‐Based Composites from UPE/EML Blends, Natural Fibers, and Nanoclay. Issue 11 (17th June 2014) - Haq, Mahmoodul; Burgueño, Rigoberto; Mohanty, Amar K.; Misra, Manjusri
<x xml:space="preserve">Abstract</x> Hybrid bio‐based composites from blends of petroleum and vegetable oil resins reinforced with natural fibers and nanoclay platelets can lead to synergistic property enhancements from the multi‐scale constituents. Twelve material designs with average hemp fiber content of 30 wt%, varying nanoclay, up to 5 wt%, and epoxidized methyl linseedate (EML), up to 30%, in unsaturated polyester (UPE) were processed and their tensile, impact, and moisture properties were experimentally characterized. The resulting biocomposites displayed synergistic behavior with the effects of bio‐resin addition being complemented by nanoclay and vice versa. Optimal performance with balanced properties (stiffness, toughness, and resistance to moisture absorption) was observed in material systems with 2.5 wt% nanoclay and up to 20% EML. Overall, hybrid biocomposites show promise in applications that require excellent stiffness‐toughness balance.<inline-graphic xlink:href="ark:/27927/pgh2ck9dvmw" content-type="mame201300473-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />